INDONESIA’S CLIMATE DIPLOMACY IN ADDRESSING GLOBAL CLIMATE CHANGE (2015–2023) - Maulidina, Salsabila Zahra; Hapsari, Renitha Dwi (The Indonesian Journal of Social Studies, 2025)
This study aims to analyze Indonesia's climate diplomacy in an effort to address global climate change from 2015 to 2023. The method used is a literature study and document analysis from various sources, including government reports, scientific journals, and policy documents related to climate diplomacy. The results of the study show that Indonesia has committed to reducing greenhouse gas emissions through the Enhanced Nationally Determined Contribution (NDC), with a target of reducing emissions by 31.89% independently and 43.20% with international assistance. Indonesia's climate diplomacy integrates domestic and global interests, and involves various initiatives such as the REDD+ scheme and the Climate Village (ProKlim) program that encourages community participation. Although there has been progress in mitigation and adaptation, challenges such as the conflict between economic development and environmental conservation remain obstacles. The conclusion of this study confirms that Indonesia's climate diplomacy not only contributes to reducing emissions, but also has the potential to be a model for other countries in facing the challenges of global climate change. With an inclusive approach and strong commitment, Indonesia can create a new narrative on climate justice and sustainability at the international level.